PERENCANAAN PREVENTIVE MAINTENANCE PADA MESIN FRAIS AJAX UNIVERSAL MODEL N° 2A Mᵏ V DI LABORATORIUM TEKNIK MESIN POLITEKNIK MANUFAKTUR NEGERI BANGKA BELITUNG - Dika Qomara Sari; Zaldy Kurniawan; Pristiansyah Pristiansyah (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
The use of the machine in a relatively long time will result in the ability of the machine to decrease and can cause damage to the machine, to make the machine in good condition, maintenance is necessary. The problem that occurs in the milling machine in the mechanical engineering laboratory of the Bangka Belitung State Manufacturing Polytechnic is that there is no maintenance procedure, based on these problems, preventive maintenance will be carried out by carrying out inspections, repairs, preparation of maintenance schedules, and job specifications using fishbone method, fishbone method is a causal analysis developed by Dr. Kaoru Ishikawa analyzed the problem and its causes in a fishbone framework. After arranging the schedule, the results were obtained for preventive maintenance with a cycle that was carried out once every 9 months for 13 years.